The organization of global negotiations : constructing the climate change regime - Depledge, Joanna (Sterling, VA : Earthscan, 2005)
'Using a theatrical metaphor, this book describes the enormous and skilful organization required by the UN to create an effective international regime, producing the UN Framework Convention on Climate Change, The Kyoto Protocol and the subsequent Bonn and Marrakesh Accords. It identifies six key elements that determine the necessary condition for successful outcomes'--Provided by publisher
Includes bibliographical references (p. [243]-252) and index
Keywords: Climatic changes -- International cooperation; Environmental policy -- International cooperation